2014
DOI: 10.1007/978-3-319-07127-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Cognitive Bias through the Use of Serious Games: Effects of Feedback

Abstract: Abstract.A serious video game was created to teach players about cognitive bias and encourage mitigation of both confirmation bias and the fundamental attribution error. Multiplayer and single-player versions of the game were created to test the effect of different feedback sources on bias mitigation performance. A total of 626 participants were randomly assigned to play the single player/multiplayer game once or repeatedly. The results indicate the single player game was superior at reducing confirmation bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Stronger forms of training can be effective. Computer games and simulations [34] provide immediate feedback, structured learning environments, and tailored instructions based on performance [16,26,58,60]. They have proven useful in reducing the fundamental attribution error, bias blind spot, and confirmation bias [16,60], after the session and even eight weeks later.…”
Section: Improve Educationmentioning
confidence: 99%
“…Stronger forms of training can be effective. Computer games and simulations [34] provide immediate feedback, structured learning environments, and tailored instructions based on performance [16,26,58,60]. They have proven useful in reducing the fundamental attribution error, bias blind spot, and confirmation bias [16,60], after the session and even eight weeks later.…”
Section: Improve Educationmentioning
confidence: 99%
“…Moreover, Kopecky et al (2016) found that, in many cases, watching the related video twice did not result in significantly greater learning gains than a single viewing. Finally, several studies conducted during development of the games failed to find significant differences in learning outcomes between 30-min and 60- to 75-min versions of the games (Dunbar et al, 2014; Veinott et al, 2013). Taken together, these findings suggest that the duration of the intervention is not sufficient to explain the observed differences in learning outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are many forms of training. One form is to use games to counter the negative impact of cognitive biases 28. Another possible form is to provide simple training programs identifying the cognitive biases and examples of such biases 25…”
Section: Introductionmentioning
confidence: 99%